Exceptionally long-range haplotypes in Plasmodium falciparum chromosome 6 maintained in an endemic African population. (December 2016) - Amambua-Ngwa, Alfred; Danso, Bakary; Worwui, Archibald; Ceesay, Sukai; Davies, Nwakanma; Jeffries, David; D'Alessandro, Umberto; Conway, David
Abstract Background Previous genome-wide analyses of single nucleotide variation inPlasmodium falciparum identified evidence of an extended haplotype region on chromosome 6 in West Africa, suggesting recent positive selection. Such a pattern is not seen in samples from East Africa or South East Asia, so it could be marking a selective process specific to West Africa. Analyses of the haplotype structure in samples taken at different times could give clues to possible causes of selection. Methods This study investigates chromosome 6 extended haplotypes in The Gambia by analysing alleles at multiple microsatellite loci using genome sequence data previously obtained from clinical isolates collected in 2008, followed by genotyping of 13 loci in 439 isolates from 1984, 1991, 2008 and 2014. Temporal changes in haplotype structure and frequencies were determined. Results A region of high linkage disequilibrium spanning over 170 kilobases (kb) was identified with both NGS and laboratory determined microsatellite alleles. Multiple long haplotypes were found in all temporal populations from The Gambia. Two of the haplotypes were detected in samples from 1984 and 1991. The frequency of long-range haplotypes increased in 2008 and 2014 populations. There was higher Fst between older and more recent populations at loci in proximity to genes involved in drug metabolism pathways. Conclusions The occurrence of several long haplotypes at intermediate frequencies suggests an unusual mode of selection in chromosome 6, possibly combined with recombination suppression on specific haplotypes. Such selection apparently occurred before the emergence of known anti-malarial drug resistance alleles, and could be due to effects of other drugs or unknown processes that have long been operating in this endemic region.